What Drives Gift-giving Intention in Live Streaming? The Perspectives of Emotional Attachment and Flow Experience - Li, Yi; Peng, Yi (International journal of human-computer interaction, 2021)
Gift-giving is popular in live streaming, and many users irrationally send virtual gifts to their favorite live streamers. Based on the attachment and flow theories, we applied the stimulus-organism-response model to explore the influence of live streamer characteristics (trustworthiness, expertise, attractiveness) and live scene characteristics (telepresence, instant feedback, interactivity, entertainment) on users' gift-giving intention through emotional attachment and flow experience. Four hundred and three valid responses to a survey questionnaire were analyzed. Findings of the research results include three aspects. First, live streamer characteristics (trustworthiness and attractiveness) can stimulate users' emotional attachment to a live streamer, thus promoting users' gift-giving intention. Second, live scene characteristics (telepresence and entertainment) can stimulate users' flow experience in live streaming. Third, users' flow experience influences their emotional attachment to live streamer.